2014
DOI: 10.1186/2193-1801-3-392
|View full text |Cite
|
Sign up to set email alerts
|

PTSD symptoms as a consequence of breast cancer diagnosis: clinical implications

Abstract: It is a well-established multidisciplinary practice at the European Institute of Oncology, that nurses and physicians often report their difficulties to clinical psychologists regarding adherence to hospital scheduling and procedures, when faced with women who, having been diagnosed with cancer, may be too overwhelmed to understand medical advice. We thus undertook an observational-prospective-cohort study, to investigate the prevalence and variation of PTSD symptomatology in women awaiting a mastectomy at a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 25 publications
1
42
0
4
Order By: Relevance
“…These symptoms decreased over time, 16.5% had PTSD symptoms at 4-month follow-up; 12.6% at the second follow-up. Also, other studies confirmed these results 4,5,10,12…”
Section: Resultssupporting
confidence: 63%
“…These symptoms decreased over time, 16.5% had PTSD symptoms at 4-month follow-up; 12.6% at the second follow-up. Also, other studies confirmed these results 4,5,10,12…”
Section: Resultssupporting
confidence: 63%
“…2 Cancer diagnosis and treatment are unique, long-term traumatic stressors, as first described by PTSD field trials for the DSM-IV. 6 There is limited knowledge about how the rates of PTSD and other psychiatric disorders among patients with cancer may differ according to nation, region, and culture. [3][4][5] PTSD is an especially pertinent issue in cancer given its association with maladaptive patterns of avoidance behavior, which may increase the likelihood of nonadherence with cancer surveillance or treatment and poorer cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] PTSD is an especially pertinent issue in cancer given its association with maladaptive patterns of avoidance behavior, which may increase the likelihood of nonadherence with cancer surveillance or treatment and poorer cancer outcomes. 6 There is limited knowledge about how the rates of PTSD and other psychiatric disorders among patients with cancer may differ according to nation, region, and culture. [7][8][9] Findings from the BQUAL study, 7 which focused on symptoms of PTSD among oncology patients up to 6 months after their initial cancer diagnosis, suggest that Asian patients with cancer may be at greater risk of PTSD symptoms compared with patients of Caucasian descent.…”
Section: Introductionmentioning
confidence: 99%
“…Intrusion is characterized by unbidden thoughts and images, troubled dreams, strong pangs or waves of feelings, and repetitive behavior (Horowitz, Wilner, & Alvarez, 1979). Breast cancer patients diagnosed with high levels of intrusion and avoidance tend to maintain up to two years after diagnosis (Arnaboldi et al, 2014), and the frequency of intrusive thoughts seems to be positively related to psychological distress (Vickberg, Bovbjerg, DuHamel, Currie, & Redd, 2000). Post traumatic symptoms were found to persist even after recovery from cancer (Amir & Ramati, 2002).…”
mentioning
confidence: 99%